Relatório de Estágio Profissional na empresa Covet House - Regado, Alexandre Assunção (2022)
e-Commerce is a field of increasing interest for many businesses, as an online store is a sales channel that is available anytime, anywhere. This competitive advantage is seen by organizations as an excellent opportunity to sell their products in new markets and to new users at a reduced cost compared to traditional methods. Covet House has recognized all the advantages of e-Commerce but needs to restructure its online store by updating its processes and improving the overall user experience. This restructuring is the central issue of this report, which aims to describe all the work done during the master's internship at this company and subsequent conclusions. To identify the problems that were threatening the performance of the online store, the Design Thinking methodology was used, which due to its focus on the user and on continuous improvement through iteration of its phases manages to provide the researcher with greater freedom to apply the various phases of the methodology at different stages of the research. After identifying and defining the various issues that hindered the purchase process and affected the user experience of the Covet House consumer, the rest of the internship period was dedicated to solving the problems identified to meet the user preferences. Upon completion of the internship the various KPI's taken before and after the internship period will be compared to understand if the changes made were able to solve the problems identified. After the final analysis and comparison of the results, it was possible to conclude that the delimited objectives were met and that the improvements implemented had the expected results. After the end of the internship, a list with more improvements to be implemented in the future was given to the host organization.